The increase of Ultisol productivity based on intercropping cassava with peanut and soybean - ARIEF HARSONO; HERDINA PRATIWI (Nusantara Bioscience, 2017)
Harsono A, Pratiwi H. 2017. The increase of Ultisol productivity based on intercropping cassava with peanut and soybean. Nusantara Bioscience 9: 157-163. The research aimed to determine the productivity and economic benefits of intercropping cassava with peanut and soybean on Ultisol dryland. Field experiment covering 2 ha land was conducted at Ultisol in East Lampung during 2011 growing season. A split plot design was used in this research involving four farmers as replications. Each farmer applied two fertilizer packages for the main plot, i.e., (A) ½ dose of recommended NPK + organic fertilizer + biofertilizer, and (B) the recommended dose of NPK. The sub-plot was intercropping system, i.e., (i) the farmer’s monoculture cassava technological package, (ii) the improved farmer’s monoculture cassava technological package, (iii) intercropping cassava + peanut, and (iv) intercropping cassava + peanut +/ soybean. The results indicated that improvement of plant spacing and NPK fertilization could increase the productivity of the farmer’s monoculture cassava technological model by 54-85% of fresh roots. The productivity could be further increased by intercropping cassava with peanut, or intercropping cassava + peanut/+ soybean. The LER of intercropping cassava + peanut was 3.30 when the technological farmer’s monoculture cassava was used as the control in the LER calculation and was 1.78 when the improved technological monoculture cassava was used as the control in the LER calculation. In addition, the LER of intercropping cassava + peanut +/soybean was 3.70 and 1.98, respectively, when the calculation of LER considered, respectively, the farmer’s monoculture cassava and improved monoculture cassava as the control. The intercropping system significantly increased the net income of monoculture system up to 210% and the higher income was generated by intercropping cassava + peanut +/soybean. The use of organic and biological fertilizer reduced the NPK fertilizer requirement by 50% and significantly increased the benefit-cost ratio.